A conceptual model of knowledge work productivity for software development process: Quality issues - Yusoff, Mohd Zairol; Mahmuddin, Massudi; Ahmad, Mazida (2012)
Knowledge is considered as the main competitive asset of the organization.Work on the knowledge work productivity has barely begun, but the most important contribution that management needs to construct in the 21st century is not only to increase the productivity of knowledge work and knowledge workers in the new century.The quality of knowledge work productivity are becomes pivotal in the context of software development today.Software development is a knowledge-intensive activity and its success depends heavily on the developers’ knowledge and experience. A conceptual model will be proposed on a way describing organization to improve quality of knowledge work productivity. The methodology begins with a reviewing a theoretical foundation and expert review that provides the scientific basis for knowledge work productivity specifically for software development. A questionnaire will be constructing in order to investigate the relationship between factors of knowledge work and quality of productivity on knowledge work. The respondents are software developers from Small Manufacturing Enterprise(SME). The data will be analyzed using Structural Equation Modeling (SEM) to identify the significant direct relationship effect among the factors. The proposed model will be helpful for the software developers to understand the determinant factors for knowledge works productivity.